MEMBANGUN ETOS KERJA UNGGUL BAGI CALON APARATUR SIPIL NEGARA: STUDI KASUS PADA TARUNA POLITEKNIK PENERBANGAN MEDAN - Nabilah, Salsabil; Sirait, Donna N.M.; Akbar, Muhammad Caesar; Lumban Gaol, Erwin (Penerbit Lafadz Jaya, 2024)
This study aims to analyze and identify the factors that contribute to the formation of a superior work ethic for State Civil Apparatus (ASN) candidates through a case study of Medan Aviation Polytechnic cadets. A strong work ethic among ASN has an important role in creating effective and quality public services. Qualitative research methods were used in this study, with in-depth interviews and participatory observation as the main data collection techniques. The results of the study indicate that there are several main factors that contribute to the formation of a superior work ethic among Medan Aviation Polytechnic cadets. First, a supportive educational environment, including an institutional culture that encourages discipline, responsibility and dedication to public service tasks. Second, effective leadership development and provision of strong values of integrity, which shape the character of ASN candidates to be more professional and ethical. Third, collaboration with government agencies and practical training that is directly relevant to ASN tasks, which helps connect theory with field practice. In conclusion, the formation of a superior work ethic for ASN candidates at the Medan Aviation Polytechnic involves a number of key factors, including a supportive educational environment, effective leadership development, and collaboration with related agencies. This research provides an in-depth look at how educational institutions can play a role in shaping the character and work ethic needed to become qualified and professional civil servants in the future.